Design, Synthesis, and Evaluation of 2, 9‐Bis[(substituted‐aminomethyl)phenyl]‐1, 10‐phenanthroline Derivatives as G‐Quadruplex Ligands. (3rd January 2017) - Gueddouda, Nassima Meriem; Hurtado, Miyanou Rosales; Moreau, Stéphane; Ronga, Luisa; Das, Rabindra Nath; Savrimoutou, Solène; Rubio, Sandra; Marchand, Adrien; Mendoza, Oscar; Marchivie, Mathieu; Elmi, Lilian; Chansavang, Albain; et al.
Abstract: Genomic sequences able to form guanine quadruplexes (G4) are found in oncogene promoters, in telomeres, and in 5′‐ and 3′‐untranslated regions as well as introns of messenger RNAs. These regions are potential targets for drugs designed to treat cancer. Herein, we present the design and syntheses of ten new phenanthroline derivatives and characterization of their interactions with G4‐forming oligonucleotides. We evaluated ligand‐induced stabilization and specificity and selectivity of ligands for various G4 conformations using FRET‐melting experiments. We investigated the interaction of compound1 a (2, 9‐bis{4‐[(3‐dimethylaminopropyl)aminomethyl]phenyl}‐1, 10‐phenanthroline), which combined the greatest stabilizing effect and specificity for G4, with human telomeric sequences using FRET, circular dichroism, and ESI‐MS. In addition, we showed that compound1 a interferes with the G4 helicase activity of Saccharomyces cerevisiae Pif1. Interestingly, compound1 a was significantly more cytotoxic toward two human leukemic cell lines than to normal human blood mononuclear cells. These novel phenanthroline derivatives will be a starting point for further development and optimization of potent G4 ligands that have potential as anticancer agents. Abstract : G4 to the fore : Guanine quadruplexes (G4) are found in oncogene promoters, telomeres, and messenger RNA introns, and are potential targets for anticancer drugs. Herein, we present the design and synthesis of ten new phenanthroline derivatives and characterization of their interactions with G4‐forming oligonucleotides. Ligand‐induced stabilization and specificity and selectivity of these derivatives for various G4 conformations were evaluated. These new compounds are starting points for further development of potent G4 ligands with anticancer potential.